Clinical pathways and patient-related outcomes in hospital-based settings: a systematic review and meta-analysis of randomized controlled trials: Clinical pathways and outcomes - Trimarchi, Laura; Caruso, Rosario; Magon, Giorgio; Odone, Anna; Arrigoni, Cristina (Acta Biomedica Atenei Parmensis, 2021)
Clinical pathways represent a multi-disciplinary approach to translate clinical practice guidelines into practical interventions. The literature from 2010 onward regarding the efficacy of adopting a clinical pathway on patient-related outcomes within the in-hospital setting has been not synthesized yet. For this reason, this systematic review and meta-analysis of randomized controlled trials aimed to critically synthesize the literature from 2010 onward about the efficacy of clinical pathways, compared with standard of care, on patient-related outcomes in different populations, and to determine the effects of clinical pathways on patient outcomes. We searched PubMed, Scopus, CINAHL, and reference lists of the included studies. Two independent reviewers screened the 360 identified articles and selected fifteen eligible articles, which were evaluated for content and risk of bias. Eleven studies were finally included. Given the commonalities of the measured outcomes, a meta-analysis including eight studies was performed to evaluate the effect size of the associations between clinical pathways and quality of life (OR=1.472 [0.483–4.486]; p=0.496), and two meta-analyses, including four studies, were performed to evaluate the effect sizes of the associations between clinical pathways with satisfaction (OR=2.226 [0.868–5.708]; p=0.096) and length of stay (OR=0,585 [0.349–0.982]; p=0.042). Reduced length of stay appeared to be associated with clinical pathways, while it remains unclear whether adopting clinical pathways could improve levels of quality of life and satisfaction. More primary research is required to determine in specific populations the efficacy of clinical pathways on patient-related outcomes.